Analysis of the state of the art on Team Management in SMEs. - Puerta Guardo, Fabio Andrés; Cantillo Orozco, Ana Susana; Merlano Chacón, Roy Alexander; Landazury Villalba, Luis Fernando; Rodríguez Gaviria, Ronald Enrique; Ortiz Martínez, Juan Manuel; Puerta Guardo, Fabio Andrés; Cantillo Orozco, Ana Susana; Merlano Chacón, Roy Alexander; Landazury Villalba, Luis Fernando; Rodríguez Gaviria, Ronald Enrique; Ortiz Martínez, Juan Manuel (Corporación Universitaria Americana, 2023)
The objective of this research was to analyze the evolution of team management in projects in SMEs in recent years from a bibliometric analysis, determining through the most representative authors, results were the most cited publications, associated factors and years of publication, as well as methodologies and procedures of investigations found. For the development of this study, a search was carried out in the Scopus database and Web of Science in English and Spanish by combining keywords such as Team Management, Human-resource Management, SME, Gestión de Equipos, Pyme. For the bibliometric analysis, scientific literature was selected based on the following criteria: Original research and / or review in English or Spanish, taking into account that it was the same criteria used for the searches for works carried out in the 2010-2020 period. Among the findings, it is worth highlighting the importance of human resource management for the achievement of objectives in SMEs and how it contributes to the process improvement. Other authors conclude that it is not related to correct functioning of SMEs whether they are managed individually or in teams.